CSCW - Four Characters in Search of a Context - Bannon, Liam J.; Schmidt, Kjeld (DAIMI Report Series, 1989)
The title of this paper was chosen to highlight the fact that the label CSCW, although widely adopted as the acronym for the field of Computer Supported Cooperative Work, has been applied to computer applications of very different ilk. It is not at all clear what are the unique identifying elements of this research area. This paper provides a framework for approaching the issue of cooperative work and its possible computer support. The core issues are identified and prospects for the field are outlined.